ANALISIS KETEPATAN KODE NEOPLASMA DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Edy Susanto; Siti Masrochah; Subinarto .; Lina Umboro Setyowati (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
The type of study is quantitative descriptive with cross sectional study. The population of this study are neoplasm patients in September-Desember 2015 about 429 patients, with the sample are 81 documents. The sample collected by Simple Random Sampling technique. In this study, data collected by observation and noted with check list. Data analyzed by description and served using table. The result showed that the number of neoplasm cases at Sultan Agung Hospital of Semarang in February and March in 2016 are 414 patient. The accuracy of neoplasm code at Sultan Agung Hospital of Semarang is 0% accurate and 100 % inaccurate for morphological code. Then the neoplasm code is  48% accurate and 52 % inaccurate